2021
DOI: 10.1177/0954405420986098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of incremental sheet metal forming process using newly designed multipoint tool with the existing single point tool by optimization and characterization methods on austenite stainless steel 202

Abstract: Incremental Sheet metal Forming (ISF) is a reliable process of converting a blank to work piece with better outputs compared to conventional forming process. The flexibility of ISF in producing the rapid prototype based on the customer needs is increased which is also desirable in the industry. But Single Point Incremental Forming (SPIF) process takes more time to form a product and hence the longer time is a barrier in implementing this process in industries. In this research work, the ISF process was made on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Ramkumar et al (2021) carried out an experimental investigation on FLD, fractography and 3D-surface roughness on Cr/Mn/Ni/Si-based stainless steel using SPIF and multi-point incremental forming (MPIF) process; the sheet is deformed using the MPIF process and it was observed that higher plastic deformation and good surface finish were achieved as compared with those achieved using the SPIF process because of more contact area in MPIF process. Kathalingam et al (2021) studied and reported that austenite stainless steel achieved good surface finish, the grease used as lubricant in MPIF process as compared with SPIF process.…”
Section: Introductionmentioning
confidence: 99%
“…Ramkumar et al (2021) carried out an experimental investigation on FLD, fractography and 3D-surface roughness on Cr/Mn/Ni/Si-based stainless steel using SPIF and multi-point incremental forming (MPIF) process; the sheet is deformed using the MPIF process and it was observed that higher plastic deformation and good surface finish were achieved as compared with those achieved using the SPIF process because of more contact area in MPIF process. Kathalingam et al (2021) studied and reported that austenite stainless steel achieved good surface finish, the grease used as lubricant in MPIF process as compared with SPIF process.…”
Section: Introductionmentioning
confidence: 99%
“…Few research works are available in MPIF [15][16][17]. In this study, three input parameters namely feed, speed and step depth are used to experimentally study their influence on surface roughness.…”
Section: Durante Et Al[6]compared Experimental and Analytical Results...mentioning
confidence: 99%
“…The forming operation is carried out up to the fracture point of the sheet metal part. The input parameters selected based on previous works [17] are selected and their levels are shown in Table 1. Step depth C 0.2 0.4 0.6 mm Total 9 experiments were conducted and coconut oil is used as the lubricant for all the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Basak et al 21 found higher formability for lower tool diameter and step depth, while higher feed rate increased productivity at the cost of surface quality in SPIF of AA6061 sheet. Kathalingam et al 22 achieved higher formability with good surface finish and less forming time in case of MPIF compared to that of SPIF process. Incremental forming of laminated sheets made of metallic and polymeric sheets was also studied by researchers as discussed below.…”
Section: Introductionmentioning
confidence: 99%